Regulatory Compliance as Substitute Legitimacy: Financial Determinants of Sustainability Reporting Quality in Indonesia's Financial Sector - Septiani Septiani; Taufik Akbar (Politeknik Siber Cerdika Internasional, 2026)
Background: Indonesia’s mandatory sustainability reporting under POJK 51/2017 has transformed financial-sector disclosure practices; however, reporting quality remains uneven, with only 4 of 89 assessed companies achieving an “Excellent” status (OJK, 2023). Objective: This study examines whether profitability (ROA), leverage (DER), and audit quality (Big Four affiliation) determine Sustainability Reporting Quality (SRQ) among financial-sector firms listed on the Indonesia Stock Exchange during 2020–2023. Methods: Grounded in Legitimacy Theory and Stakeholder Theory, this study uses a balanced panel dataset of 103 firms (412 observations). SRQ is operationalised as a Sustainability Reporting Disclosure Index (SRDI) covering 61 items from the GRI Universal Standards. A Fixed Effects Model (FEM) with White robust standard errors was selected based on the Chow Test (F = 4.614; p < 0.001) and Hausman Test (χ² = 8.278; p = 0.041). Results: Profitability (t = −1.920; p = 0.151), leverage (t = −1.190; p = 0.320), and audit quality (t = 1.303; p = 0.284) do not demonstrate significant partial effects on SRQ; however, the model is statistically significant overall (F = 5.277; p < 0.001; R² = 64.42%). The significant intercept (C = 0.489; p < 0.001) indicates the existence of a “regulatory floor,” a mandatory minimum baseline of sustainability disclosure (approximately 29 of 61 GRI items) achieved consistently by all firms regardless of their financial characteristics. This condition reflects the coercive isomorphic pressure imposed by POJK 51/2017. Conclusion: By positioning SRQ as a policy instrument, this study proposes the adoption of graduated, quality-based sustainability governance to strengthen transparency, accountability, and inclusive economic development in emerging economies.